Carbachol- and elevated Ca(2+)-induced translocation of functionally active protein kinase C to the brush border of rabbit ileal Na+ absorbing cells. - Cohen, M E (1991)
Protein kinase C is involved in mediating the effects of elevated Ca2+ in ileal villus Na+ absorbing cells to inhibit NaCl absorption. The present studies were undertaken to understand the mechanism by which this occurs. The effects of carbachol and the calcium ionophore A23187, agents which elevate intracellular Ca2+ and inhibit NaCl absorption in ileal villus cells, were studied. Carbachol treatment of villus cells caused a rapid decrease in protein kinase C activity in cytosol, with an accompanying increase in microvillus membrane C kinase. Exposure of the villus cells to calcium ionophore also caused a quantitatively similar decrease in cytosol C kinase and increase in C kinase activity in the microvillus membrane. This increase caused by carbachol and Ca2+ ionophore was specific for the microvillus membrane. In fact, 30 s and 10 min after exposure of the cells to carbachol, basolateral membrane protein kinase C decreased, in a time-dependent manner; whereas 10 min of Ca2+ ionophore exposure did not alter basolateral C kinase. Exposure of villus cells to Ca2+ ionophore or carbachol caused similar increases in microvillus membrane diacylglycerol content. As judged by the ability to inhibit Na+/H+ exchange measured in ileal villus cell brush border membrane vesicles, the protein kinase C which translocated to the microvillus membrane was functionally significant. Inhibition of Na+/H+ exchange required ATP and was reversed by the protein kinase C antagonist H-7. In conclusion, the effect of carbachol and Ca2+ ionophore in regulation of ileal NaCl absorption is associated with an increase in microvillus membrane diacylglycerol content and functionally active protein kinase C. The effects of both carbachol and Ca2+ ionophore are different on brush border and basolateral membrane distribution of protein kinase C.